1991
DOI: 10.1080/09540129108253047
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in social support and mental health in men with HIV infection: A pilot study

Abstract: The mediating role of social support in the mental health and behaviours of persons coping with life-threatening chronic illness is of potentially great importance in determining the quality of life of persons with HIV infection (PWHs). As part of a biracial pilot study of the ways black and white men manage the stresses of sexually acquired HIV infection, we have examined the relationship between social support and mental health and behaviours. Forty homosexual/bisexual men (20 white and 20 black) attending a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…This negative association between social support and mood disturbance has been shown in other studies of HIV-infected gay men (Namir, Alumbaugh, Fawzy, & Wolcott, 1989;Rabkin, Williams, Neugebauer, Remien, & Goetz, 1990;Zich & Temoshok, 1987). However, in their small biracial sample (N = 40), Ostrow (Ostrow et al 1991) found that social support was negatively correlated with psychological distress among white gay men but positively correlated among African American gay men. The authors interpreted this finding to suggest limited satisfaction with the social support available to these minority men.…”
mentioning
confidence: 71%
“…This negative association between social support and mood disturbance has been shown in other studies of HIV-infected gay men (Namir, Alumbaugh, Fawzy, & Wolcott, 1989;Rabkin, Williams, Neugebauer, Remien, & Goetz, 1990;Zich & Temoshok, 1987). However, in their small biracial sample (N = 40), Ostrow (Ostrow et al 1991) found that social support was negatively correlated with psychological distress among white gay men but positively correlated among African American gay men. The authors interpreted this finding to suggest limited satisfaction with the social support available to these minority men.…”
mentioning
confidence: 71%
“…Along with HIV stigma in the general community and potential rejection from partners, 37 some men fear being questioned about how they were infected and being associated with a Bgay disease.^8 Other documented complications with being identified as HIV-infected include potential rejection from family, friends, and religious communities and physical harm. 8,[38][39][40] The threat of losing the love and protection of family or religious standing within a cultural context where family and church are central and act as a buffer against racial and socioeconomic oppression, may be particularly untenable for NGI African American MSM/W. These data provide insight into how NGI HIV-positive African American MSM/W perceive safer sex, experience living with HIV, and decide to whom to disclose their HIV status.…”
Section: African American Msm/w and Hiv Transmissionmentioning
confidence: 89%
“…Inverse correlations between social support and depression have been found in numerous samples of HIV-positive individuals (Nott et al, 1995;Ostrow et al, 1991;Siegel et al, 1994). Further, longitudinal studies have found that social support directly contributes to later mental health in this population (Hays et al, 1992;Lackner et al, 1993aLackner et al, , 1993bSiegel et al, 1997).…”
Section: Introductionmentioning
confidence: 94%
“…Further, longitudinal studies have found that social support directly contributes to later mental health in this population (Hays et al, 1992;Lackner et al, 1993aLackner et al, , 1993bSiegel et al, 1997). Social support has beneficial effects on self-reported quality of life (Friedland et al, 1996), overall well-being (Ostrow et al, 1991), and adjustment to AIDS (Rodgers, 1995), and is related to lower levels of loneliness (Gant & Ostrow, 1995), hopelessness (Zich & Temoshok, 1987), and general distress (Wolcott et al, 1986). Support has also been associated with fewer physical symptoms, better perceived health, and improved immune function (Namir et al, 1989;Pakenham et al, 1994;Wolcott et al, 1986).…”
Section: Introductionmentioning
confidence: 97%